Mysterium Pansophicum: imaginário e esoterismo em Jacob Boehme - Batista Segundo, João Florindo (2017)
Jacob Boehme (1575-1624) was a shoemaker and mystic whose prophetic work gave support to Christian Theosophy and through imaginatio vera bequeathed subsidy to an imaginary simultaneously source and effluvium of Western esotericism. In addition to the manufacture of footwear, which only protects the feet of the pedestrians, the esoteric learning (practical and speculative) has made him the craftsman of a penetrating unveiling of the road to nature, as a power and expressiveness of the transcendent. In this reflection, we examine the ideas of the author allusive to theogony, cosmogony, anthropogony, cosmology and eschatology, in short, to the landmarks with which the man endeavors to apprehend the numinous and delimit his meaning. The imagination has a prominent place in Görlitz?s Shoemaker?s work, which is why, among the methodological tools to understand it, we have opted for those linked to the General Imaginary Theory (TGI), with emphasis on symbolic hermeneutics and figurative structuralism from the Durandian investigations. The present research as to the means is bibliographical, as far as the ends is exploratory and had as base logic the hypoteticaldeductive method. Initially, the text presented here intends to know the socio-cultural context in which Boehme was inserted, to seek to unravel what he called Mysterium Pansophicum, a concept exposed in his writings, rich in images (literary and pictorial). Without intending to exhaust the thought of the Teutonic Theosophist, this research aims at providing a convenient contribution to the Sciences of Religions in its interface with the field of Western esotericism, still little explored by the Brazilian scholarly study.